Peningkatan Keterampilan Membaca Nyaring Melalui Media Pias-Pias Kata pada Siswa Kelas I SDN 1 Mojorejo Ponorogo - PUTRI, LINDA MATARINA KARTIKA (Trapsila: Jurnal Pendidikan Dasar, 2019)
This classroom action research was conducted on grade 1 students of SD Negeri 1 Mojorejo Ponorogo 2014/2015 Academic Year, due to the existence of problems, namely the learning outcomes of Indonesian language subjects especially reading aloud were still low. Through word-of-mouth media this problem is tried to be improved and improved. The design of this study was to use classroom action research (PTK) methods which aimed to improve or improve the quality of continuous learning practices. The study was conducted at SD Negeri 1 Mojorejo Ponorogo and the students studied were grade 1 students totaling 20 students. The implementation of classroom action research was carried out in two cycles. In one cycle consists of four steps, namely (1) planning (2), 2) actions or actions (acting), (3) observations (observing), (4) reflection (reflecting). Instruments used in learning are implementation plans learning (RPP), and research instruments namely observation sheets and activity sheets. Data collection is done by observation and performance testing techniques. Data analysis uses the mean. The results of this study can be seen by the increase in reading skills of students with the following values: in the pre-cycle the average value was 57.50 (35%), in the first cycle the average score was 70.00 (60%), and in cycle II the average value rose again to 81.75 (95%). Based on the data mentioned above, it can be said that through the word pias media it is very effective to improve the ability to read aloud to grade 1 students of SD Negeri 1 Mojorejo Ponorogo in 2014/2015 Academic Year.